Influence of preoperative light vaginal bleeding for perinatal adverse outcomes on physical examination-indicated cerclage. (3rd July 2021) - Kawamura, Hiroshi; Hayashi, Shusaku; Takaoka, Sachi; Mabuchi, Aki; Yamamoto, Ryo; Ishii, Keisuke; Mitsuda, Nobuaki
Abstract: Purpose: To clarify the relationship between light vaginal bleeding (LVB) before physical examination-indicated cerclage (PEIC) and perinatal adverse outcomes. Methods: This was a retrospective cohort study involving 94 singleton pregnancies undergoing PEIC <26 weeks of gestation at a single perinatal medical center between 2008 and 2015. The primary outcome was set as spontaneous preterm birth (sPTB) <34 weeks of gestation. The secondary outcomes were set as the second-trimester loss prior to 22 weeks of gestation, sPTB before 28 weeks of gestation, sPTB before 37 weeks of gestation, and stillbirth or neonatal death. Relationships between LVB and adverse outcomes were evaluated using logistic regression analysis. Results: Preoperative LVB was detected in 16 cases (17.0%). Multivariate logistic regression analyses revealed that preoperative LVB was an independent risk factor for sPTB <34 weeks of gestation (adjusted odds ratio [aOR]: 8.42; 95% confidence interval [CI]: 1.72–41.1; p  < .01), sPTB <28 weeks of gestation (aOR: 5.98; 95% CI: 1.67–21.4; p  < .01) and perinatal death (aOR: 8.47; 95% CI: 1.11–64.5; p  = .04). Conclusions: Vaginal bleeding prior to PEIC, even nonsignificant or self-limiting, is associated with sPTB before 28 or 34 weeks of gestation and perinatal death.